Judicial Balacing of Parental Objection to Medical Treatment on the Basis of Religious Beleifs and Children Right to Life in Nigeria - Eyongndi, David Tarh-Akong; Adeniji, Samuel A. (The Age of Human Rights Journal, 2022)
Children being vulnerable, have special protection under the law through their parents or guardian who are responsible for them; and make decisions for them because they lack legal capacity. One of these decisions a parent/guardian makes is determining the religion of a child. Once the parent/guardian chooses the religion of the child, the child may become bound by its practices throughout childhood. While the right of parents to determine the religion of their children is recognised by domestic, regional and international laws, the way courts in Nigeria treat this recognition suggests that the right is not absolute. This paper adopts the doctrinal methodology in interrogating the extent to which Nigerian Courts permit the observation by a child of the religious practices of his/her parent in relation to submission to medical treatment in order to protect the child’s right to life. This paper argues that law and morality are media of social control but have their convergence and divergence. It further argues that sanctity of human life which for many forbids suicide, requires that even adults should not be allowed to object to medical treatment which refusal may result in death which can be seen as “disguised suicide.” These authors examined the Supreme Court decision in Medical Dental Practitioners Disciplinary Council v. Okonkwo and found that; Nigerian Courts recognise parent right to choose their children religion and practices however, any religious practice prejudicial to the child based on the “best interest” principle provided under the Child Right Act and its States equivalent will be jettisoned. It examines the practice in Britain and Canada and draw lessons for Nigeria. This paper recommends public enlightenment, prohibition of harmful religious beliefs such as objection to life-saving medical procedure by parents for minors as means of balancing parents/guardian right to choose their children religious beliefs and preservation of the children right to life.